Penerapan Bermain Puzzle Gambar Melalui Metode Kerja Kelompok dalam Meningkatkan Sikap Mau Membantu pada Anak Usia 4-5 Tahun Di TK Aisyiyah 1 Tidung - Umi Kusyairy; Nurul Qalbi; M. Rusdi T; Muzakkir; Sunu Prihatin (Faculty of Tarbiyah and Teacher Training, 2022)
Social development in children, especially in an attitude of wanting to help, is very important to be stimulated from an early age, because it is fundamental for children to interact with people around them. This study aims to determine the attitude of wanting to help after the application of playing picture puzzles through the group work method in children aged 4-5 years. This community service research in the form of service learning was conducted at Aisyiyah 1 Tidung Kindergarten with 3 children as participants. The instruments used are picture puzzles, observation sheets for children and evaluation sheets for the implementation of the intervention. Data were analyzed using descriptive statistics. The results of the service research show that children are able to realize and increase their willingness to help their friends in playing picture puzzles by using the group work method.